ANALYSIS OF POWER SUPPORT BEHIND PILE AND GIRDER BRIDGE ABUTMENT RANDUMERAK LOAD ON VERTICAL AND HORIZONTAL - Dimas Wahyu Tri Pamungkas; Helmy Darjanto (Neutron, 2019)
Construction of pile foundations is also called a foundation in construction enabled to heavy loads (high rise building). Before the implementation of the construction of the first construction is implemented and carried out in the field is the work of the foundation (bottom structure). Foundation work itself is very important for civil engineering works, because this is the foundation that secures simultaneously carry the load working on the construction. This study aimed to analyze the carrying capacity and the forces acting on the pile working from the Standard Penetration Test (SPT), the data kalendering pile installation time, then the data terbebut in include into the application to determine how far the resilience of construction are already working. Methodology The data collection is done by making observations, collecting data from the project and conduct a literature study. From the analysis of the structure obtained by the forces at work in the use of the calculation of the structure. The calculations show that the pile cap and slab reinforcement in accordance with the moment that occurs, the strength and bearing capacity of the pile meet safety requirements.